Unveiling Male Hegemony: A Comparative Study of Nathaniel Hawthorne's The Scarlet Letter and Ahmad Tohari's Bekisar Merah - Olga A. Rorintulus (Journal of English Culture, Language, Literature and Education, 2023)
This comparative study delves into the nuanced realms of women's resistance against male hegemony in two literary works from distinct cultural and temporal contexts: Nathaniel Hawthorne's "The Scarlet Letter" and Ahmad Tohari's "Bekisar Merah." This study adopted qualitative descriptive approach for the design while for data analysis, comparative through literary feminism study was employed. Through a meticulous analysis and comparative of the narratives, characters, and society’s landscapes depicted in both novels, the study unveils the pervasive presence of male hegemony and its impact on women's lives. As the findings, this study shed light on the multifaceted nature of male hegemony, illustrating its manifestations across different cultural and society contexts. By examining the dynamics of resistance enacted by female characters in both novels, the study revealed the male hegemony, gender dynamics and women resistance in each novel, this would contribute to a deeper understanding of the universal challenges women face in patriarchal societies. This exploration underscores the significance of women's agency and resistance as they navigate the complex web of societal expectations, ultimately challenging and redefining the boundaries of gender roles. In light with these findings, scholars can enrich the discourse surrounding male hegemony, gender dynamics, and women's resistance in literature. Moreover, through this study, further researchers are encouraging to foster a more comprehensive and nuanced understanding of the intricate relationships between power, gender, and resistance in literary narratives.